Miskonsepsi siswa smp pada materi perbandingan dengan menggunakan four tier diagnostic test - Sama Al-Qonuni; Ekasatya Aldila Afriansyah (Jurnal Inovasi Pembelajaran Matematika: PowerMathEdu, 2023)
One obstacle that occurs in the learning of junior high school students in solving complex and abstract problems is characterized by a misunderstanding of concepts (misconceptions). One effort to find out the misconception is to use the Four Tier Diagnostic Test (FTD Test). While the material used in this study is a comparison material that is synonymous with the concept of a comparison. This study aims to determine the type of misconception and causes of misconceptions experienced by students on comparison material using FTD Test. This type of research is descriptive research with a qualitative approach. The subjects in this study were 5 Class VIII-D students of SMPN 1 Tarogong Kaler as many as 5 people were chosen using the Purposive Sampling method. The instruments used in this study were FTD Test sheets, interview guidelines, and observation sheets. Data were analyzed using data reduction techniques, data presentation, and data verification1/drawing conclusions. The results of this study students experience classification misconceptions, correlational misconceptions, and theoretical misconceptions. The cause of misconceptions in students is from their own students who do not understand the comparison material, the teacher's habit of giving routine practice questions, and is also influenced by learning online. Salah satu hambatan yang terjadi pada pembelajaran siswa SMP dalam memecahkan permasalahan yang kompleks dan abstrak ditandai dengan adanya kesalahpahaman konsep (miskonsepsi). Salah satu upaya untuk mengetahui adanya miskonsepsi adalah dengan menggunakan Four Tier Diagnostic Test (FTD Test). Materi yang digunakan dalam penelitian ini adalah materi perbandingan yang identik dengan konsep perbadingan. Penelitian ini bertujuan untuk mengetahui jenis miskonsepsi dan penyebab miskonsepsi yang dialami oleh siswa dengan menggunakan FTD Test. Jenis penelitian yang digunakan adalah deskriftif dengan pendekatan kualitatif, dengan subjek penelitian adalah siswa kelas VIII-D SMPN 1 Tarogong Kaler sebanyak 5 orang yang dipilih dengan menggunakan metode purposive sampling. Instrumen yang adalah lembar FTD Test, lembar pedoman wawancara, dan lembar observasi. Data dianalisis menggunakan teknik reduksi data, penyajian data, dan verifikasi data/penarikan kesimpulan. Hasil dari penelitian ini siswa mengalami miskonsepsi klasifikasional, miskonsepsi korelasional, dan miskonsepsi teoritikal. Penyebab terjadinya miskonsepsi kurangnya memahami materi perbandingan, kebiasaan guru memberi soal latihan rutin, dan juga dipengaruhi oleh pembelajaran yang dilakukan secara daring.